CNS Involvement in Chronic Inflammatory Demyelinating Polyneuropathy: Subtle Retinal Changes in Optical Coherence Tomography - Ingwersen, Jens; Graf, Jonas; Kluge, Julia; Weise, Margit; Dietrich, Michael; Lee, John-Ih; Harmel, Jens; Hartung, Hans-Peter; Ruck, Tobias; Meuth, Sven G; Albrecht, Philipp; Aktas, Orhan; et al. (Neurology® neuroimmunology & neuroinflammation, 2022)
BACKGROUND AND OBJECTIVES: Chronic inflammatory demyelinating polyneuropathy (CIDP) is an autoimmune disease primarily affecting the peripheral nervous system. However, several noncontrolled studies have suggested concomitant inflammatory CNS demyelination similar to multiple sclerosis. The aim of this study was to investigate an involvement of the visual pathway in patients with CIDP. METHODS: In this prospective cross-sectional study, we used high-resolution spectral-domain optical coherence tomography to compare the thickness of the peripapillary retinal nerve fiber layer and the deeper macular retinal layers as well as the total macular volume (TMV) in 22 patients with CIDP and 22 age-matched and sex-matched healthy control (HC) individuals. Retinal layers were semiautomatically segmented by the provided software and were correlated with clinical measures and nerve conduction studies. RESULTS: In patients with CIDP compared with healthy age-matched and sex-matched controls, we found slight but significant volume reductions of the ganglion cell/inner plexiform layer complex (CIDP 1.86 vs HC 1.95 mm3, p = 0.015), the retinal pigment epithelium (CIDP 0.38 vs HC 0.40 mm3, p = 0.02), and the TMV (CIDP 8.48 vs HC 8.75 mm3, p = 0.018). The ganglion cell layer volume and motor nerve conduction velocity were positively associated (B = 0.002, p = 0.02). DISCUSSION: Our data reveal subtle retinal neurodegeneration in patients with CIDP, providing evidence for visual pathway involvement, detectable by OCT. The results need corroboration in independent, larger cohorts.
Keywords: Polyradiculoneuropathy, Chronic Inflammatory Demyelinating; lidé; Middle Aged; Adult; zrakové dráhy; Tomography, Optical Coherence; prospektivní studie; Female; Visual Pathways; nervové vedení; Neural Conduction; retina; Retina; Humans; průřezové studie; Prospective Studies; Cross-Sectional Studies; lidé středního věku; optická koherentní tomografie; mužské pohlaví; ženské pohlaví; chronická zánětlivá demyelinizační polyneuropatie; Male; Aged; dospělí; senioři